Anticancer Effects of Nutraceuticals in the Mediterranean Diet: An Epigenetic Diet Model - DIVELLA, ROSA (Cancer Genomics Proteomics, 2020)
Epidemiological and clinical studies support the association between nutrition and development or progression of different malignancies such as colon, breast, and prostate cancer, defining these tumors as diet-associated cancer. The Mediterranean diet shows inverse associations with metabolic diseases, cardiovascular pathologies and various types of cancer. Many bioactive nutrients of the Mediterranean diet have been identified as factors protective against these types of pathologies. The epigenome has been identified as the primary goal of modulations in gene expression related to these molecular nutrients. In fact, they can modify the epigenome and can be incorporated into the ‘epigenetic diet’, which translates into a diet regimen that can be used therapeutically for health or preventative purposes. Most epigenetic changes are influenced by lifestyle and nutrition. Epigenetic therapy is a new area for the development of nutraceuticals whose absence of toxicity can represent a valid asset in cancer prevention strategies. Recent advances in understanding the mechanisms of nutrigenomics, nutrigenetics and nutraceuticals have led to the identification of superfoods capable of favorably conditioning gene expression. In this review, we highlight the importance of nutraceuticals present in the Mediterranean diet as epigenetic modifiers both in the mechanisms of tumor onset and as protective agents.